Origin of Improved Optical Quality of Monolayer Molybdenum Disulfide Grown on Hexagonal Boron Nitride Substrate. Issue 2 (25th November 2015) - Wan, Yi; Zhang, Hui; Wang, Wei; Sheng, Bowen; Zhang, Kun; Wang, Yilun; Song, Qingjun; Mao, Nannan; Li, Yanping; Wang, Xinqiang; Zhang, Jin; Dai, Lun
Abstract : Monolayer MoS2 is synthesized on hexagonal boron nitride (h‐BN) flakes with a simple, high‐yield method. Monolayer MoS2 on h‐BN exhibits improved optical quality. Combining the theoretical and experimental analysis, it is concluded that the enhanced photoluminescence and Raman intensities of monolayer MoS2 probably originate from the relatively weak doping effect from the h‐BN substrate rather than the optical interference effect.